Internet-based anti-vaccination lobbying in South Africa - Moloi, Molelekeng Hildegard (University of Limpopo (Medunsa Campus), 2011)
Background and aim: The development of vaccines is considered one of the greatest achievements of biomedical science and public health, because it has led to the reduction of the global burden of infectious diseases. However, vaccination has become a victim of its own success, since most parents have not been exposed to epidemics of vaccine-preventable diseases, and now some fear the vaccines more than the diseases that they prevent. Globally, there is a growing number of parents who use the internet to seek advice on vaccination, and unfortunately some of this advice is anti¬vaccination (A V). Some studies have analyzed vaccine criticism on the internet, but none have focused on South Aftica (SA). The purpose of this study was to identify the characteristics of the anti¬vaccination lobby on SA internet sites including blogs using search terms that were specifically aimed at increasing the retrieval of A V sites. Methods: A structured internet search was conducted on SA web pages using Google, Yahoo, and MSN search engines, for keywords "don't vaccinate", "vaccination is harmful", "should not vaccinate", " not vaccinating", "vaccination causes harm", "against vaccines", etc. The words "immunization" and "immunisation" were also substituted for the word "vaccination" in these searches. These A V sites were then extracted for analysis of content and authors. Results: The overall coverage of SA A V websites was 30.2% (19/63), with Google identifying the most A V sites (59.3% [16/27]), compared to 33.3% (9/27) for Yahoo and 7.4% (2/27) for MSN. Of these A V sites 42.1 % (8/19) were identified to be blogging sites. The A V advocates included 36% (5/14) mothers / parents, 26% (4/14) business people, and 21% (3/14) journalists. The main concerns identified included vaccine safety and efficacy, ethical concerns, and claimed financial profit motives. There were 32% (6/19) of the authors who referenced or posted articles written by other A V lobbyists from the USA. Conclusion: The A V advocates on SA internet are individuals who are independently lobbying against child vaccination and not a cohesive A VL group. The concerns they raised are similar to those raised by A VL from the USA. The SA population is therefore exposed to influences on the internet both ftom local and international views. The internet blogs and forums are an important platform for sharing A V views in an informal manner.
Thesis (MPH) -- University of Limpopo, 2011.
Keywords: Vaccination